1985
DOI: 10.1128/mcb.5.3.466
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation and tumor promoter treatment increase levels of a transcript for a secreted glycoprotein.

Abstract: The major excreted protein of transformed mouse fibroblasts, a secreted, mannose 6-phosphate-containing glycoprotein, is induced in nontransformed cells by a variety of transforming agents, by phorbol esters, and by platelet-derived growth factor. We report here the molecular cloning of the cDNA encoding this protein and demonstrate that its induction is a consequence of enhanced mRNA levels for major excreted protein in both tetradecanoyl phorbol acetate-treated 3T3 cells and 3T3 cells transformed by a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1985
1985
1997
1997

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…It is well known that malignant transformation of mouse cells by a variety of agents results in increased synthesis and secretion of 39 kD protein termed major excreted protein (MEP) (18,25). Recent cloning of the cDNA of the protein has shown that it is identical with the cysteine proteinase, cathepsin L (17).…”
Section: ) Secretion Of Cysteine Proteinasesmentioning
confidence: 99%
“…It is well known that malignant transformation of mouse cells by a variety of agents results in increased synthesis and secretion of 39 kD protein termed major excreted protein (MEP) (18,25). Recent cloning of the cDNA of the protein has shown that it is identical with the cysteine proteinase, cathepsin L (17).…”
Section: ) Secretion Of Cysteine Proteinasesmentioning
confidence: 99%
“…We have recently isolated several recombinant cDNA clones containing MEP sequences and identified a single 1.8-kilobase (kb) MEP RNA transcript in NIH/3T3 cells (15). Absolute levels of MEP mRNA increased after treatment of 3T3 cells with TPA or after transformation by a number of oncogenes, including v-ras or c-ras.…”
mentioning
confidence: 99%
“…secreted abundantly from mouse tumour cells (Gottesman & Yuspa, 1981 ;Doherty et al, 1985), precipitated C37-I RNA-encoded polypeptides of sizes similar to those reported earlier in translation of unselected polyadenylated RNAs from transformed mouse fibroblasts. Preincubation of anti-LTR serum with free peptide II abolished its reactivity with polypeptides synthesized in vitro from MMTV RNA (not shown).…”
Section: Resultsmentioning
confidence: 82%